Issue Information. (4th March 2020) - Unknown
Abstract : Cover : In Prommersberger et al. (https://doi.org/10.1002/cpim.93 ), Efficacy of lentiviral gene transfer. CD8‐positive T cells were activated (Day 1, 3/3) and lentivirally transduced (Day 2) with a transgene encoding for CAR and truncated EGFR as transduction marker. 6 days after transduction, cells were stained with CD8‐VioBlue and EGFR‐specific antibody to detect the CAR + cells. Cells were subjected to analysis on a Miltenyi MACSQuant flow cytometer. Gates were set on Lymphocytes (FSC/SSC) and CD8 + T cells.